2006
DOI: 10.1203/01.pdr.0000220361.08181.c3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Protein Restriction in Rats on Cardiac Fibrosis and Capillarization in Adulthood

Abstract: This study examines the effect of maternal protein restriction in rats on levels of cardiac fibrosis, myocardial capillarization, and media:lumen ratio of intramyocardial arteries in adult offspring. Female Wistar Kyoto rats were fed either a normal protein diet (NPD; 20% casein) or a low-protein diet (LPD; 8.7% casein) during pregnancy and lactation. Female offspring (seven per group) were weaned at 4 wk of age and grown to adulthood. At 24 wk of age, the offspring were perfusion fixed. Cardiac fibrosis and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 34 publications
6
53
0
2
Order By: Relevance
“…The relative increase in heart size in the LPD offspring is probably the result of increased collagen deposition within the myocardium; there was a marked increase in interstitial fibrosis within the myocardium of the IUGR offspring. These findings are in accordance with previous findings in our laboratory; earlier, we observed a 15% increase in interstitial fibrosis in the hearts of LPD offspring at 24 wk of age (16). A similarly significant increase in interstitial fibrosis has been described in adolescent guinea pigs that were growth restricted in utero because of chronic placental insufficiency (27).…”
Section: Altered Cardiac Growth In Offspring With Iugrsupporting
confidence: 93%
See 1 more Smart Citation
“…The relative increase in heart size in the LPD offspring is probably the result of increased collagen deposition within the myocardium; there was a marked increase in interstitial fibrosis within the myocardium of the IUGR offspring. These findings are in accordance with previous findings in our laboratory; earlier, we observed a 15% increase in interstitial fibrosis in the hearts of LPD offspring at 24 wk of age (16). A similarly significant increase in interstitial fibrosis has been described in adolescent guinea pigs that were growth restricted in utero because of chronic placental insufficiency (27).…”
Section: Altered Cardiac Growth In Offspring With Iugrsupporting
confidence: 93%
“…In animal models, there is clear evidence of cardiac programming in IUGR offspring as a result of prenatal hypoxia (15). In the rodent maternal protein restriction model, previous studies have shown increased collagen deposition in the hearts of IUGR offspring by early adulthood (24 wk of age) (16) and overt cardiac dysfunction in these animals by 40 wk of age (17). Therefore in this study we proposed that IUGR acts as an initial insult to the developing heart, rendering it more vulnerable to secondary postnatal insults.…”
mentioning
confidence: 99%
“…Importantly, our dietary regime of maternal protein restriction differs from many other laboratories in that the rat dams were administered the LPD for 2 wk before mating, throughout pregnancy and for 2 wk during lactation (6,7,12). Indeed, there have been a number of recent studies demonstrating the importance of not only the intrauterine environment but also the periconceptional and lactational environment in determining the long-term growth profile of the offspring (24 -27).…”
Section: Discussionmentioning
confidence: 99%
“…From 24 wk of age, animals were housed individually for measurement of dietary intake. At 32 wk of age, the rats were perfusion fixed (12). The pancreas and visceral fat (epididymal and intra-abdominal) were excised and weighed.…”
mentioning
confidence: 99%
“…The female rats were divided into two groups and fed either a normal-protein diet (NPD) that contained 20% casein or a low protein diet (LPD) that contained 8.7% casein for 2 weeks before mating (to familiarize the dams to the diets), during pregnancy, and 2 weeks after birth (as cardiomyocytes continue to proliferate in the first 2 weeks postnatally in rats) (Lim et al, 2006). After this time, all dams were fed normal laboratory chow.…”
Section: Animals and Diet Treatmentmentioning
confidence: 99%